Dysphagia due to Multiple Esophageal Rings - Stephen N Sullivan (Canadian Journal of Gastroenterology)
A 27-year-old Saudi man with dysphagia due to multiple esophageal rings is reported and the literature reviewed. Dysphagia due to multiple esophageal rings is very rare. Only 15 cases have been reported. The patient is usually male and has had dysphagia for many years when presenting. The cause of the rings is unknown. Theories to explain dysphagia are that the rings are either congenital or an unusual manifestation of gastroesophageal reflux.